High Risk in Loss Insurance in The Perspective of Conventional Insurance and Syariah Insurance - Zanariyah, Sri; Famulia, Ledy; Renaldi, Rendy (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study examines the risk management of tabarru funds of sharia insurance at PT Asuransi Bumiputera Muda 1967 Serang. The aim is to determine the differences in principle between the conventional insurance system and the sharia insurance system in regulating high-risk issues. This study is classified as doctrinal legal research (normative juridical) which is descriptive and analytical in nature based on data obtained through a literature review. This study found differences in tendencies between conventional insurance and sharia insurance in responding to high risks in a guaranteed contract. According to the conventional insurance system, high risks occurring at the implementation stage of the agreement can result in the termination of the insurance agreement. However, if the high risk has been calculated from the beginning of the contract and agreed upon by both parties, then the contract will continue following the agreement stated in the policy. In contrast to this principle, the sharia insurance system applies the principle of ta'āwun (mutual assistance) where each insurance participant donates their funds to other participants who are affected by disasters, regardless of the risk being low or high. Thus it can be concluded that in conventional insurance the relationship that occurs is between individuals and the company while in sharia insurance all insurance participants are collectively bound to the company and share the risk (transfer risk).